The impact of risk factors associated with long-term computer use on musculoskeletal discomfort among administrative staff: A case study - Fazilah, Abdul Aziz; Nur Aqila, Nor Azmi (Penerbit UMP, 2022)
Work-related musculoskeletal diseases (WMSDs) are on the rise as a result of excessive usage of desktop computers. People use computers in the office for communication, word processing, data processing, record keeping, and project management, among other applications. This study aimed to determine the prevalence of musculoskeletal discomfort (MSD) and related risk factors among university workers. This study explores the association between the severity of body discomfort and affected activities such as daily living and work. This study focused on musculoskeletal discomfort among support staff at University Malaysia Pahang who works in the office. There is 50 support staff (58 percent were females; 47 percent were males) who participated in this cross-sectional study. Nordic Musculoskeletal Questionnaire (NMQ) was used to gather data on personal characteristics, occupational conditions, and the prevalence of WMSDs. The intensity of pain was assessed using a Visual Analogue Scale (VAS). This study found four body regions with the most pain experienced by office workers: neck, shoulders, upper back, and low back. The individual risk factors related to musculoskeletal discomfort are age, weight, and height. The occupational risk factors that are most significant are working experience, daily computer use, and virtual meetings during work from home (WFH). Work and leisure activities are the most affected by the pain experienced by the respondents. In terms of work aspects, this study determined that job performance is the most significantly affected due to musculoskeletal discomfort. This study gives office workers some awareness of risk factors related to musculoskeletal discomfort during prolonged computer use and prolonged sitting. Providing prolonged computer use guidelines to reduce musculoskeletal discomfort among office workers is highly recommended.